(untitled) (Transactions of the Association of European Schools of Planning, 2020)
Before the Covid-19 pandemic, and according to a debate promoted by Benjamin Davy, we decided to have a special issue of the Transactions of the Association of European Schools of Planning on the intersections of human dignity, planning, and urban spaces. The articles in this special issue were written before the pandemic emergency, but nevertheless make a significant contribution in reflecting on the mutual relationships between human dignity and control of spaces, in ordinary as well as extraordinary times.